Changes in household waste generation and composition during Covid-19 pandemic, case study in 8 districts of Arequipa, Perú - Requena Sanchez, Norvin Plumieer (2021)
In Peru the COVID-19 pandemic led to a strict quarantine since March 15th, in the city of Arequipa this situation prevailed until September 17th when measures were slowly loosen up. This state of emergency has produced a series of environmental changes on water and air quality and also changes in waste generation and composition, however the latter data has not been equally collected and disseminated. This case study presents the results of waste characterization from 25 households in 8 districts in the province of Arequipa. The Technical Team of Solid Waste form the Environmental Engineering Faculty of the National University of Engineering conducted the study. Data from waste generation and segregation habits was gathered and, after receiving the appropriate training, participants provided information about their household waste generation and composition (between the 1st and 7th of September). The generation per capita of the study was 0.373 kg/hab./day, this value is less than the registered for the province of Arequipa (0.49 kg/hab./day) which can be explained by a reduction on the family purchasing power during the quarantine. On the waste composition is important to notice the elevated percentage of food leftovers (15.53%), this can be due to an increase on the cooking frequency, food prepared, inadequate product storage or excess in edibles purchased.